Meta-analysis of genome-wide association studies to assess C-reactive protein response to statin therapy. (25th February 2016) - Deshmukh, Harshal; Chasman, Daniel; Trompet, Stella; Li, Xiaohui; Sun, Fangui; Hitman, Graham; Colhoun, Helen
Abstract: Background: We have recently shown that the C-reactive protein (CRP) response to statin therapy is highly variable, with 45% of people on atorvastatin having no decrease in CRP. Whether there is any genetic component to this variability is unclear. We sought to identify genetic determinants and quantify the single nucleotide polymorphism based heritability of CRP response to statins. Methods: In a meta-analysis of genome-wide association studies, we included datasets from both randomised controlled trials and observational studies. There were about 10 000 statin-treated individuals overall, grouped into a first discovery stage (from the CARDS trial and PROSPER, PARC, and FSH studies) and a second replication stage (from the JUPITER trial). CRP response was modelled as log(CRP follow-up/CRP baseline) adjusted for baseline CRP and other covariates. Genome-complex trait analysis (GCTA) was used to identify the narrow-sense heritability of CRP response. Findings: The study consisted of about 5300 statin users in the discovery cohort and 4000 statin users as replication cohort. On the GCTA analysis narrow-sense heritability ( h 2 ) for CRP response was 0·19 (SE 0·24) and was higher than that reported for LDL cholesterol response to statin therapy 0·05 (SE 0·14). Preliminary results of the genome-wide association meta-analysis identified three loci that achieved genome-wide statistical significance: APOE, rs429358 (p=7·91E–10); RP11-458D21.5, rs184819447 (p=2·32E–9); MYT1L, rs79020661 (p=3·21E–8). Other than APOE none of these was associated with LDL response to statin therapy or baseline CRP. Interpretation: These data are consistent with statin-induced change in CRP having a mechanism distinct from LDL cholesterol change. We identified several loci associated with CRP-response to statin therapy and they need to be investigated further by additional replication analysis. Funding: HD is funded by a National Institute for Health Research Clinical Academic Fellowship.